Efektivitas Penggunaan Teknologi Mobile Health dalam Peningkatan Self Management Pasien Diabetes Mellitus Tipe-2 - Indraswari, Anies Dewi Wirati; Yulia, Yulia; Hariyati, Rr. Tutik Sri (Journal of Telenursing (JOTING), 2024)
This review aim to evaluate effectiveness of mobile health (mHealth) technology on self management of Type 2 Diabetes Mellitus (T2DM) patients based on evidence from various studies. The method employed in this review included a systematic search of articles from PubMed, Scopus, and Embased databases using the keywords “mobile health and diabetic”, mobile health and diabetes”, dan “mobile health and diabetes mellitus”. The analysis was conducted on 1,479 articles, from which 12 met the inclusion criteria. The findings of this review reveal that the utilization of mHealth whether in the form of application or text messages, has the potential to enhance self-management, particularly in diet regulation, physical activity, blood glucoseoo monitoring, medication adherence, and doctoro visits among T2DM patients. mHealth technolgy has proven effective in improving self-management T2DM patients. Keywords : Diabetes Mellitus, Mobile Health, Self Management, Smartphone.